Lana Granger’s Post-Traumatic Stress Disorder in Lisa Unger’s In The Blood - Ranita Camellia Pamuncak; R. Aj. Atrinawati (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
This paper analyzes the main character, Lana Granger, in Lisa Unger’s In The Blood. The aim of this study is to explain the Post-Traumatic Stress Disorder (PTSD] portrayed by Lana Granger. The analysis includes the causes, the symptoms, the effects, and the development of Lana’s PTSD throughout the story. The writer uses psychological approach to analyze the story and library research as method of data collection. The writer uses textual and contextual methods to analyze the novel. The contextual method supported by the concept of trauma and the concept of PTSD by the American Psychiatric Association and Gerald C Davidson. The result of the analysis shows that Lana Granger has shown all symptoms of PTSD after experiencing major traumatic event in her life. It also shows that trauma affects Lana social life, personality, and identity. The social supports obtained by Lana from his aunt and his best friend play important roles in the process of his healing journey from PTSD.Keywords: traumatic event; trauma; PTSD; mental health